Impact of moderate pump–Stokes chirp on femtosecond coherent anti‐Stokes Raman scattering spectra - Gu, Mingming; Satija, Aman; Lucht, Robert P. (Journal of Raman spectroscopy, 2020)
The effects of inducing moderate chirp in the pump and Stokes beams in chirped‐probe‐pulse femtosecond coherent anti‐Stokes Raman scattering (CARS) spectroscopy are discussed. This is an important issue for measurements in high‐pressure systems where the CARS beams must be transmitted through glass of significant thickness to reach the probe volume of interest. The effects were investigated both experimentally, by inserting disks of SF‐11 glass into the pump and Stokes beam paths, and theoretically, by incorporating pulse chirp into our time‐dependent density matrix (TDDM) simulations. Experimentally, we found that inducing moderate pump and Stokes chirp produced significant spectral narrowing of the nonresonant four‐wave mixing contribution to the CARS signal, and this allowed us to control the resonant excitation bandwidth to eliminate interferences from neighboring species. The temperature measurement accuracy and precision were essentially unchanged with respect to the unchirped pump and Stokes case. The effect of moderate pump and Stokes chirp on the narrowing of the Raman excitation efficiency envelope was investigated by solving the full set of TDDM through direct numerical integration. The numerical efficiency of the solutions was enhanced dramatically by developing a parallel version of the TDDM code. The calculated Raman excitation efficiency profile was incorporated in our phenomenological spectral fitting codes. Effects of frequency chirp on N2 CPP fs CARS spectrum are presented. The nonresonant signal bandwidth is significantly narrowed by adding moderate amount of frequency chirp, and the degradation of Raman excitation efficiency can be accounted by performing time‐dependent density matrix calculations. The accuracy of flame thermometry obtained through N2 CPP fs CARS measurement is not significantly affected for moderately chirped pump and Stokes pulses.